Development of advanced NO sub x control concepts for coal-fired utility boilers - Evans, A.; Newhall, J.; England, G.; Seeker, W. R. (Energy and Environmental Research Corporation, 1992)
CombiNOsub x is a NOsub x reduction process which incorporates three different NOsub x control technologies: reburning, selective non-catalytic reduction (SNCR), and methanol injection. Gas reburning is a widely used technology that has been proven to reduce NOsub x up to 60% on full-scale applications. The specific goals of the CombiNOsub x project are: 70% NOsub x reduction at 20% of the cost of selective catalytic reduction; NOsub x levels at the stack of 60 ppm for ozone non-attainment areas; Demonstrate coal reburning; Identify all undesirable by-products of the process and their controlling parameters; Demonstrate 95% N0{sub 2} removal in a wet scrubber. Before integrating all three of CombiNOsub x's technologies into a combined process, it is imperative that the chemistry of each individual process is well understood. Pilot-scale SNCR tests and the corresponding computer modeling were studied in detail and discussed in the previous quarterly report. This quarterly report will present the results obtained during the pilot-scale advanced reburning tests performed on EER's Boiler Simulation Facility (BSF). Since methanol injection is a relatively new NOsub x control technology, laboratory-scale tests were performed to better understand the conditions at which methanol is most effective. The experimental set-up and results from these tests will be discussed.